2004
DOI: 10.1161/01.res.0000150594.95988.45
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor α Induces NADPH Oxidase Activity in Macrophages, Leading to the Generation of LDL with PPAR-α Activation Properties

Abstract: Abstract-Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors controlling lipid and glucose metabolism as well as inflammation. PPARs are expressed in macrophages, cells that also generate reactive oxygen species (ROS). In this study, we investigated whether PPARs regulate ROS production in macrophages. Different PPAR-␣, but not PPAR-␥ agonists, increased the production of ROS (H 2 O 2 and O 2 . ) in human and murine macrophages.PPAR-␣ activation did not induce cellular toxicity, but signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 42 publications
(22 reference statements)
7
81
2
2
Order By: Relevance
“…To date, NADPH oxidase is the most thoroughly investigated ROS-generating system. Recent studies have implicated induction of NADPH oxidase via PPAR␣ as the main molecular source of PPAR␣ agonist-induced ROS (34). Contrary to these reports, our data suggest that DEHP can induce increases in glomerular NADPH oxidase proteins without involvement of PPAR␣.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, NADPH oxidase is the most thoroughly investigated ROS-generating system. Recent studies have implicated induction of NADPH oxidase via PPAR␣ as the main molecular source of PPAR␣ agonist-induced ROS (34). Contrary to these reports, our data suggest that DEHP can induce increases in glomerular NADPH oxidase proteins without involvement of PPAR␣.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, macrophages play a major role in development of atherogenesis through low-density lipoprotein oxidation and such effects are, at least in part, mediated by NADPH oxidase-derived superoxides (18,49). In addition, during chronic inflammation, production of superoxides by recruited macrophages may drive carcinogenesis by damaging neighboring epithelial or stromal cells (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature demonstrates conflicting effects on fibrates in the in vitro setting. Studies in macrophages demonstrate that PPARα activation leads to increased superoxide and hydrogen peroxide production via an upregulation of NADPH oxidase subunits, p47phox, p67phox and gp91phox [48]. Conversely, studies in endothelial cells demonstrated a decrease in p22phox and p47phox and increased antioxidant expression with fibrate therapy [49].…”
Section: Discussionmentioning
confidence: 99%